Crescimento de mudas de Pinus oocarpa Schiede em diferentes condições hídricas e de adubação - Silva, José Mauro Santana da [UNESP] (2007)
The aim of this work was to compare the final development of Pinus oocarpa Schiede seedlings using tree different underwater depth and with or without coverage fertilization. The research was done inside on a glass green house at the UNESP - College of Agronomical Science, Rural Engineering Department (Botucatu - SP - Brazil). Two trials were done to evaluate biomass, seedling height and diameter development. The first trial, using underground water on 17 cm, 31 cm and 45 cm depth, with or without coverage fertilization with N-P-K. The second trial was done with 28 flowerpots (12 liters each) and 3 seedlings per unit. The experimental design, used to evaluate the height and diameter growth and hydric potential and relative plant water content, was: 1- without water deficit and without coverage fertilization; 2- with water deficit and without coverage fertilization; 3- without water deficit and with coverage fertilization; 4- with water deficit and coverage fertilization. The underground water result showed that 31 cm and fertilization was better for seedling growing rather that 17 cm and without fertilization. The fertilized treatments showed higher plant high and diameter comparing to non fertilized samples, using Tukey test at 5%. For dry plant matter, the best results were obtained with 31 and 45 cm underground water level. The seedling root system dry mass was decrement along the soil profile. The treatment with underground water of 31 cm and fertilization was superior according to Tukey test at 5% of probability and the treatment with underground water of 17 cm and without fertilization was inferior for root dry mass (g). All the others treatment didn t have statistical differences. It didn t happen the irrigation effect on the plant high development; however the fertilized treatment had superior development compared to unfertilized samples. The relative water content didn t change... (Complete abstract click electronic access below)